THE EFFECTIVENESS OF VIRTUAL METACOGNITIVE LEARNING TO ANALYZE STUDENT AWARENESS, EVALUATION, AND REGULATION PROCESSES IN PROBLEM SOLVING - Dwi Purnomo; Nurcholis Sunuyeko; Rochsun Rochsun; Endang Sumarti; Anangga Widya Pradipta; Nurmala Hindun (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
AbstractThis article is the result of virtual learning research with research subjects of two groups of students and aims to determine the effectiveness of metacognitive learning so that the components of metacognition in solving problems can be analyzed. The research begins with a pre-test followed by virtual learning and ends with post-test and metacognition questionnaires. During the post-test, students' activities in solving them were observed through awareness, evaluation, and regulation while the metacognition questionnaire consisted of questions about metacognition components. The results of the data analysis show that students who do metacognition, their learning outcomes increase so that there is a relationship between the components of metacognition and the ability to solve problems. This relationship is expressed by the correlation coefficient rxy = 0.419 with the regression equation y = 61.02 + 0.287x. This means that each metacognition independent variable can increase the average problem solving dependent variable by 0.287 units. Statistically, metacognitive learning is quite effective in solving problems. Based on these final results it can be recommended that virtual learning with a metacognitive model can be used as a new way and becomes a strong motivation for students to improve their ability to solve problems. Keywords: effectiveness, metacognition questionnaire homogeneous, interpretation, virtual learning. AbstrakArtikel ini merupakan hasil penelitian pembelajaran virtual dengan subjek penelitian dua kelompok mahasiswa dan bertujuan untuk mengetahui efektivitas pembelajaran metakognitif sehingga komponen metakognisi dalam memecahkan masalah dapat dianalisis.  Penelitian diawali dengan pre-test yang dilanjutkan dengan pembelajaran virtual dan diakhiri dengan pemberian post-test dan  angket metakognisi. Selama post-test, diamati aktivitas mahasiswa dalam menyelesaikannya melalui kesadaran, evaluasi, dan regulasi  sedangkan angket metakognisi berupa pertanyaan tentang  komponen metakognisi. Hasil analisis data menunjukan mahasiswa yang melakukan metakognisi, hasil belajarnya meningkat sehingga ada hubungan antara komponen metakognisi dengan kemampuan menyelesaikan masalah. Hubungan tersebut dinyatakan oleh koefisien korelasi rxy = 0,419 dengan persamaan regresi y = 61,02 + 0,287x. Hal ini berarti bahwa setiap variabel independen metakognisi dapat meningkatkan rata-rata variabel dependen pemecahan masalah sebesar 0,287 satuan. Secara statistika  pembelajaran metakognitif cukup efektif dalam pemecahan masalah. Berdasarkan hasil akhir tersebut dapat direkomendasikan bahwa pembelajaran virtual dengan model metakognitif dapat digunakan sebagai cara baru dan menjadi motivasi yang kuat bagi mahasiswa untuk meningkatkan  kemampuan dalam menyelesaikan masalah. Kata kunci: angket metakognisi, efektivitas, homogen, interpretasi, pembelajaran virtual.